Kontribusi Pengasuhan Orangtua dan Self Esteem terhadap Perilaku Bullying - Dalimunthe, Raudah Zaimah; Marjohan, Marjohan; Syahniar, Syahniar (Konselor, 2014)
Bullying behavior is influenced by many factors. This study purpose to describe: 1) Parenting, Self-Esteem and bullying behavior, 2) Parenting and Self-esteem either individually or collectively contributed to the bullying behavior. The population of study is focus in students of SMP Negeri 6 Percut Sei Tuan, with a sample 193 of students, by using multistage random sampling technique. The instrument in this study used a Likert Scale model and inventory (CFSEI). The results of reliability test on parenting 0901 and 0938 for bullying behavior. The validity of instrument on parenting and self-esteem is 0361 and 0.361 for self- esteem. These results indicate that parenting is in good enough category and self-esteem is at a low category, bullying in middle category, and parenting and self-esteem either singly or collectively that contribute to bullying behavior.